Patterns of geomagnetic Pc1 pulsations in different solar cycles in the near-equatorial region from the Indian subcontinent - Bulusu, Jayashree; Pilipenko, Vyacheslav; Arora, Kusumita; C. Prasanna, C. Prasanna (My University, 2022)
Pc1 geomagnetic pulsations have been investigated at very low latitudes using 13 years of archived records covering solar cycle 20–21 from the equatorial site Choutuppal (CPL, L = 1.03), and 5 years of digital induction coil magnetometer data covering descending phase of solar cycle 24 from the low latitude site Desalpar (DSP, L = 1.07). At CPL, the maximum number of Pc1 events is seen in the declining phase of the solar cycle 20 and minimum occurrence is observed in the ascending phase of the solar cycle 21. In contrast, at DSP, the Pc1 occurrence shows a maximum during solar maximum and a minimum in the declining phase of solar cycle 24. The annual and seasonal patterns of Pc1 occurrence show an inverse relation with sunspot numbers at both stations. The seasonal variation of Pc1 occurrence has a maximum in December solstice at CPL and in June solstice at DSP, respectively. The diurnal variations of Pc1 activity show similar trends at both locations with maximum Pc1 occurrence during pre- and post-midnight sectors. The superposed epoch analysis shows minimum number of Pc1s in the initial phase, followed by Pc1 occurrence in the main phase, increasing significantly in the recovery phase of geomagnetic storms. The role of ionospheric plasma density and attenuation of Pc1 waves upon propagation via the ionospheric waveguide is presented.
Keywords: Pc1 pulsations; Low-latitude investigation; Solar cycle dependence; Seasonal variation; Geomagnetic storm